OP0015 Stimulation of soluble guanylate cyclase reduces experimental dermal fibrosis. (23rd January 2014) - Beyer, C.; Reich, N.; Schindler, S.C.; Distler, A.; Dees, C.; Tomcik, M.; Hirth-Dietrich, C.; von Degenfeld, G.; Sandner, P.; Distler, O.; Schett, G.; Distler, J.H.
Abstract : Background: Fibrosis of the skin and internal organs is a cardinal feature of systemic sclerosis (SSc). Since it disrupts the physiologic tissue architecture and causes organ failure, fibrosis leads to a high disease burden among patients with SSc. Thus, effective anti-fibrotic therapies, which are still not available for clinical routine, are needed urgently. During development of anti-fibrotic drugs, attention needs to be paid to other disease manifestations of SSc, in particular vascular disease. Ideal treatment strategies for SSc inhibit tissue fibrosis and may have beneficial effects on vascular disease. Objectives: To study the anti-fibrotic effects of stimulators of the soluble guanylate cyclase (sGC), a class of vasoactive drugs that are currently evaluated in phase III clinical trials for pulmonary arterial hypertension (PAH). Methods: We examined the effect of the sGC stimulator BAY 41-2272 on the release of collagen from dermal fibroblasts. We further studied the anti-fibrotic effects of BAY 41-2272 on prevention and regression of fibrosis in bleomycin-induced dermal fibrosis and in Tsk-1 mice. To study potential hypotensive effects of sGC stimulation, we performed telemetric blood pressure studies in conscious mice. Results: In vitro, sGC stimulation with BAY 41-2272 dose-dependently inhibited col1a1 and col1a2 mRNA synthesis and collagen release in dermal fibroblasts from SSc patients and healthy individuals. In vivo, BAY41-2272 prevented the increase of skin thickness, hydroxyproline content, and myofibroblast counts in the model of bleomycin-induced dermal fibrosis. These effects were dose-dependent with reductions of skin thickening by 51.7% ( p <0.001) at 1 mg/kg bid and 79.7% ( p <0.001) at 3 mg/kg bid. Apart from prevention, BAY 41-2272 was effective in the treatment of established bleomycin-induced fibrosis and induced regression of fibrosis. In the Tsk-1 mouse model, BAY41-2272 prevented hypodermal thickening by 37.0% ( p <0.001) at 1 mg/kg bid and 56.8% ( p <0.001) at 3 mg/kg bid. Hydroxyproline content and myofibroblast counts were also reduced in a dose-dependent manner. Similar to the bleomycin models, BAY 41-2272 was highly effective in the treatment of established fibrosis in a modified Tsk-1 model. Finally, treatment with sGC stimulators was well tolerated. Telemetric studies showed that relevant anti-fibrotic doses of BAY 41-2272 did not affect systemic blood pressure and heart rate. Conclusions: Our findings demonstrate potent anti-fibrotic effects of sGC stimulators in both prevention and treatment of dermal fibrosis. Of note, sGC stimulation was effective in inflammation-dependent as well as in non-inflammatory murine models of SSc, suggesting its efficacy in various clinical stages. Throughout our in vivo -experiments, sGC stimulators were well-tolerated. Given their potential vasoactive properties and their efficacy in PAH, sGC stimulators might be promising candidates for the dual treatment of fibrosis and vascular disease in SSc. Disclosure of Interest: C. Beyer: None Declared, N. Reich: None Declared, S. Schindler: None Declared, A. Distler: None Declared, C. Dees: None Declared, M. Tomcik: None Declared, C. Hirth-Dietrich Employee of: Bayer Health Care, G. von Degenfeld Employee of: Bayer Health Care, P. Sandner Employee of: Bayer Health Care, O. Distler: None Declared, G. Schett: None Declared, J. Distler Shareholder of: 4D science, Consultant for: Bayer Health Care